Market Discipline Mechanism: A Quantitative Approach (The Study of Islamic Banking in Indonesia 2011-2014) - Ayub Wijayati Sapta Pradana; Hariri Hariri; Junaidi Junaidi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
Transparency of information are the main requirement of market discipline mechanism which is described by an adequate disclosure. Through the quantitative approach, the customer will attract an investment funds (giro, savings, deposits) if the bank takes a high risk action based on information that disclosed on financial statements. In a theoretical view, Islamic banks with the principle of profit-loss sharing (PLS) have a higher risk than conventional banks with a fixed rate of interest, so that customers of Islamic banks should have a higher sensitivity than conventional bank customers. The next question, whether the customers of Islamic banks would react to the disclosure of financial statements through changes in the number of funds invested?This research aimed to examine the effect of the level of disclosure of financial statements to changes in the number of third party funds in Indonesia Islamic Banking on the period 2011-2014. Data were analyzed using a regression model. The study states that the level of disclosure of financial statements significant positive effect on changes in the number of third-party funds were indicates that there is a mechanism of market discipline on Islamic Banks in Indonesia. However, this result must to be strengthened by data of risk disclosure and ability to absorb information from customers, analysis of determinants were affecting customers behavior, then as well as the comparison test with conventional commercial banks.Keywords: market discipline, the level of disclosure, third party funds, Islamic bank